2020
DOI: 10.1186/s12875-019-1074-9
|View full text |Cite
|
Sign up to set email alerts
|

Stratified primary care versus non-stratified care for musculoskeletal pain: findings from the STarT MSK feasibility and pilot cluster randomized controlled trial

Abstract: Background: Musculoskeletal (MSK) pain from the five most common presentations to primary care (back, neck, shoulder, knee or multi-site pain), where the majority of patients are managed, is a costly global health challenge. At present, first-line decision-making is based on clinical reasoning and stratified models of care have only been tested in patients with low back pain. We therefore, examined the feasibility of; a) a future definitive cluster randomised controlled trial (RCT), and b) General Practitioner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
75
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(77 citation statements)
references
References 56 publications
1
75
1
Order By: Relevance
“…Amendments to the tool and matched treatment options were informed by bringing together the qualitative findings reported here with the quantitative findings from the feasibility and pilot trial, which are reported elsewhere (see Hill et al [17]). The changes, as outlined below, were made following a series of discussions amongst the broader TAPS trial team, as well incorporating input from members of the TAPS Trial Steering Committee and the study's PPIE group.…”
Section: Amendments To the Stratified Care Intervention Informed By Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Amendments to the tool and matched treatment options were informed by bringing together the qualitative findings reported here with the quantitative findings from the feasibility and pilot trial, which are reported elsewhere (see Hill et al [17]). The changes, as outlined below, were made following a series of discussions amongst the broader TAPS trial team, as well incorporating input from members of the TAPS Trial Steering Committee and the study's PPIE group.…”
Section: Amendments To the Stratified Care Intervention Informed By Tmentioning
confidence: 99%
“…2, below). Prior to a main trial that compares the clinical-and cost-effectiveness of stratified primary care for patients with the five most common MSK pain presentations, versus usual, non-stratified care, a feasibility and pilot RCT was needed to test the The STarT MSK feasibility and pilot RCT (ISRCTN 15366334) was a pragmatic, two parallel arm, cluster RCT and is fully described in a separate publication [17]. In brief, 8 general practices were randomised (4 to stratified care, 4 to usual care) and patients consulting with the five most common MSK pain presentations were invited to participate in data collection over 6 months.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with NP and LBP have several similarities in psychosocial prognostic factors and comorbidities, clinical guidelines for best practice, and lack of specific pathoanatomic causality [11][12][13][14]. While the models for clinical management of musculoskeletal complaints to date have mainly been condition specific, there have recently been calls for management based on characteristics within the biopsychosocial model regardless of pain condition [14][15][16][17]. Studies have also demonstrated that patients with trajectories of NP display similar on most health-related factors as for LBP [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Also, we identified one published pilot study and protocol for a trial testing stratified care in musculoskeletal conditions including OA. 39 , 40 No trials or protocols were identified on head-to-head comparisons of stepped and stratified models of care. Although there is limited research to inform whether models of care could be the same for OA and LBP or if one model should be chosen rather than the other, a recent focus group study indicated that practitioners consider a generic stratified model to be relevant across 5 musculoskeletal conditions.…”
Section: Key Message #2: It Is Not a Choice Between Stepped Care Omentioning
confidence: 99%